Sosialisasi Hukum: Kehadiran Negara Dalam Program Pendaftaran Tanah Sistematis Lengkap (Ptsl) Sebagai Kepastian Hak Atas Tanah - Muhammad Rifaldi Setiawan; Ayang Afira Anugerahayu; Ahwan; Hera Alvina Satriawan; Ade Sultan Muhammad (BALE LITERASI, 2026)
This community service activity aims to enhance public legal awareness regarding the importance of land registration through the Complete Systematic Land Registration Program (PTSL) as a form of state presence in ensuring legal certainty and protection of land rights. The background of this activity is based on the low rate of land certification and the increasing potential for agrarian conflicts due to investment pressures, particularly in Bayan Village, North Lombok Regency. The method used is Participatory Action Research (PAR), consisting of planning, implementation, evaluation, and closing stages, involving active community participation, especially the Pelita Bayan Youth Organization. The results indicate a significant improvement in public understanding, measured through pre-test and post-test. Understanding of land ownership urgency increased from 30% to 90%, knowledge of land registration procedures from 20% to 85%, and awareness of legal protection from 30% to 95%. Additionally, community participation in the PTSL program also increased substantially. This activity confirms that a preventive approach through legal socialization is effective in improving legal literacy and supporting the realization of legal certainty in the land sector.